Doing ethnography from within a constructivist paradigm to explore virtual communities in Saudi Arabia - Al-Saggaf, Yeslam; Williamson, Kirsty (Qualitative Sociology Review, 2006)
Most of the studies in the recent literature focus on the method used but not the philosophy behind it. This article focuses on doing ethnography, from within a constructivist paradigm, to explore individuals’ participation in virtual communities in Saudi Arabia. An aim of this article is to highlight how particular ethnographic techniques, viz unobtrusive observation and participation, were used in that study. The article argues that doing ethnography in this way allowed for placing the results within the social and cultural context of Saudi society. The article, which includes a sample of the findings from the two techniques involved for illustration, concludes that the one-year unobtrusive observation and the eight months’ participation in two different but similar virtual communities, during the period 2001-2002, have produced findings that are deep, meaningful and rich in description.